Rutting evaluation of hydrated lime and SBS modified asphalt mixtures for laboratory and field compacted samples - Ozen, Halit (ELSEVIER SCI LTD, 2011)
The purpose of this study is to evaluate permanent deformation for hydrated lime and SBS modified asphalt mixtures. Control (C), 2% hydrated lime (2L). 5% SBS polymer mixtures and 2%hydrated lime-5%SBS (2L5SBS) mixtures were prepared. The Laboratoire Central des Fonts et Chaussees (LCPC) wheel tracker, also known as French Rutting Tester were realized with two different stages. Same LCPC slabs were produced. Original LCPC compactors and also field cylinder were used separately. LCPC rutting values were determined with left and right wheel loadings. Also averages were obtained with calculation. Repeated creep tests were used for these mixtures and permanent deformations were plotted for two different moisture conditioning that water immersion and freeze and thaw cycles. Diameter samples (100 mm and 150 mm) were studied in repeated creep tests. In the result that LCPC tracking values were compared with repeated creep tests in terms of sample diameters. LCPC wheel-tracking test results show that 2L5SBS mixtures reveal utmost performance according to the other mixtures types. Polymer modification increased rutting resistance of lime modified ones. Both original LCPC compactor and field cylinder compaction showed resemble results. 150 mm samples showed highest correlation (higher than R-2 = 0.80) between LCPC test and repeated creep test for different compaction types and different moisture conditionings. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Asphalt mixtures; SBS polymer; Hydrated lime; LCPC test; Repeated creep test; Moisture conditioning; Correlation; PERFORMANCE; Construction & Building Technology; Engineering; Materials Science